INTEGRATING SOCIAL MEDIA PLATFORMS INTO LANGUAGE CLASSROOMS FOR ECONOMICS STUDENTS: OPPORTUNITIES AND CHALLENGES - Hafizov A. A. (Bright Mind Publishing, 2025)
Social media platforms have emerged as powerful tools for enhancing language learning, particularly for specialized academic disciplines such as economics. This article explores how social media can be effectively integrated into language classrooms to support economics students in developing linguistic proficiency alongside domain-specific knowledge. Through a mixed-methods approach, including surveys and classroom interventions, this study examines the impact of platforms like Twitter, LinkedIn, and Instagram on vocabulary acquisition, communication skills, and engagement with economic concepts. Results indicate that structured integration of social media fosters collaborative learning and contextualized language use, though challenges such as digital distractions and varying levels of technological proficiency must be addressed. Recommendations for educators include designing task-based activities and establishing clear guidelines to maximize benefits.
Keywords: Social media, language learning, economics education, technology integration, collaborative learning.